Overview of material constitutive law for additive manufacturing metal structures - Bing-Lin Lai; Yi-Ran Li; Tong Guo; George Vasdravellis; J. Y. Richard Liew (Urban Lifeline)
Abstract Metal materials play a significant role in civil and construction engineering, and additively manufactured (AM) metals are gaining attention as a complementary technology due to their benefits of reduced material waste and greater design flexibility. In recent years, AM carbon steel, stainless steel, and alloy steel have drawn considerable interest from both academia and industry; however, their material properties are not yet fully understood. This paper compiles the mechanical properties of four materials—Ti6 Al4 V, 17-4PH, 304 stainless steel, and 316 stainless steel under both monotonic tensile loading and low-cycle fatigue conditions from published literatures. It examines the effects of anisotropy, surface treatment, heat treatment, and other post-processing methods on the mechanical properties of AM metals. Finally, this paper evaluates and compares the constitutive models for AM metals subjected to both monotonic tensile and low-cycle fatigue loading, providing insights to aid in the design and analysis of AM metal structures.